Pemberdayaan Masyarakat Pedagang Krupuk Olahan di Pantai Kenjeran Surabaya - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Diana Hertati (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
One of the community empowerment programs that seek to optimize the potential of the marine and fisheries sector by the government is "Program Pemberdayaan Ekonomi Masyarakat Pesisir” (PEMP), which became the flagship program to improve the welfare of coastal communities in a structured manner through community empowerment and utilizing coastal resources optimally and sustainable but PEMP that proclaimed in 2000 failed and continued with PEMP kemuduan 2001. This failure is caused because PEMP considered not able to channel the aspirations of local communities (coastal). The program is the Family Welfare Economic Empowerment Program which is a partnership program between the villages located in the vicinity of the “Usaha Pengelolaan Pendapatan Keluarga Sejehtera” (UPPKS) based fisheries. Economic empowerment of the family welfare program focuses on community empowerment chips processed fish traders who use the main raw materials result from the sea. Economic empowerment programs aimed at improving the welfare of traders through the trade group increased production through training and processing of raw materials results from the sea.